Rancang Bangun Aplikasi E-Residence - Rikho R. Polii; Xaverius B.N. Najoan; Virginia Tulenan (Jurnal Teknik Elektro dan Komputer, 2018)
Abstract — The information is an data which is processed into one form that is very useful for this present and future. Awarness will emphasize the information and communication to people to develop computers which is to support the information. The developer information is was available in the form of applications from any other platform Android. The information enffloresce throughtout of the any others spect of human life and the availability of information in form of a gedget application makes it easy for as ti find a place to live in, sometimes everyone wants to sell their property has difficulty to sell or to looking for new property becarus of limited information. The goal of this research is to design an information application and seller based on Android. This application uses the Disciplined Agile Delivery (DAD) method. The expected of this research will facilitate and to help process of finding information and as a place to sell property, this application will provide such as information such information of property and sale of property Keywords — Android; Application; Information; Property Abstrak — Informasi adalah data yang diolah menjadi bentuk yang memiliki arti bagi penerima dan bermanfaat bagi pengambil keputusan saat ini atau mendatang. Kesadaran akan pentingnya informasi dan komunikasi mendorong orang mengembangkan teknologi komputer guna mengatasi kebutuhan informasi. Pengembangan informasi tersebut tersedia dalam bentuk aplikasi dari berbagai platform seperti android. Informasi berkembang diseluruh kehidupan aspek manusia dan  ketersediaan informasi dalam bentuk aplikasi gadget memudahkan pengguna untuk mencari tempat tinggal yang sudah direncanakan untuk di tempati, terkadanng setiap orang yang ingin menjual properti kesulitan untuk memasarkan atau mencari properti karena keterbatasan informasi. Penelitian ini bertujuan untuk merancang sebuah aplikasi sebagai sumber informasi dan penjualan berbasis android, aplikasi ini menggunakan metode  Disciplined Agile Delivery (DAD). Penelitian ini diharapkan dapat membantu memudahkan proses mencari informasi dan sebagai tempat untuk menjual properti. Aplikasi ini akan memberikan informasi properti dan penjualan properti. Kata kunci — Aplikasi; Android; Informasi; Properti